Validation and reliability of the Turkish Utian Quality-of-Life Scale in postmenopausal women. Issue 4 (April 2016) - Abay, Halime; Kaplan, Sena
Abstract : Supplemental Digital Content is available in the text Abstract: Objective: There are a limited number of menopause-specific quality-of-life scales for the Turkish population. This study was conducted to evaluate the validity and reliability of the Turkish Utian Quality-of-Life Scale in postmenopausal women. Methods: The study group was comprised of 250 postmenopausal women who applied to a training and research hospital's menopause clinic in Turkey. A survey form and the Turkish Utian quality-of-Life Scale were used to collect data, and the Turkish version of Short Form-36 was used to evaluate reliability with an equivalent form. Language-validity, content-validity, and construct-validity methods were used to assess the validity of the scale, and Cronbach's α coefficient calculation and the equivalent-form reliability methods were used to assess the reliability of the scale. Results: The Turkish Utian Quality-of-Life Scale was determined to be a valid and reliable instrument for measuring the quality of life of postmenopausal women. Confirmatory factor analysis demonstrates that the instrument fits well with 23 items and a four-factor model. The Cronbach's α coefficient for the quality-of-life domains were as follows: 0.88 overall, 0.79 health, 0.78 emotional, 0.76 sexual, and 0.75 occupational. Reliability of the instrument was confirmed through significant correlations between scores on the Turkish version of the Utian Quality-of-Life Scale and the Turkish version of the Short Form-36 ( r  = 0.745, P  < 0.001). Conclusions: This research emphasizes that the Turkish Utian Quality-of-Life Scale is reliable and valid in postmenopausal women—it is a useful instrument for measuring quality of life during menopause.